Winners and Losers: How Woody Encroachment Is Changing the Small Mammal Community Structure in a Neotropical Savanna - Furtado, Luciana O.; Felicio, Giovana Ribeiro; Lemos, Paula Rocha; Christianini, Alexander V.; Martins, Marcio; Carmignotto, Ana Paula (Frontiers in Ecology and Evolution, 2021)
Years of fire suppression, decreases in herbivores and global climate change have led to shifts in savannas worldwide. Natural open vegetation such as grasslands and shrublands are increasing in wood density, but the effects for small mammals are not well understood. While most of the mammal studies from the Brazilian Cerrado is concentrated in the core area of this large Neotropical savanna, its southern portions are suffering from biome shifting through woody encroachment. Herein, we surveyed a small mammal community from the southeastern boundary of Cerrado (Santa Bárbara Ecological Station) and evaluated the micro and macro environmental variables shaping community structure in order to investigate how the woody encroachment in the last 15 years may have influenced this assemblage. We recorded 17 species of marsupials and rodents along five distinct habitats in a gradient from grasslands to woodlands. Although richness was not affected by microhabitat variables, total and relative abundance varied according to habitat type and in relation to herbaceous, shrub and tree density. Rodents such as Calomys tener and Clyomys laticeps were positively affected by increasing herb cover, Cerradomys scotti and Oligoryzomys nigripes by shrub cover, while the marsupial Didelphis albiventris had higher association with increasing tree cover. We detected an increase of 27.4% in vegetation density (EVI) between 2003 and 2018 in our study site, and this woody encroachment negatively affected the abundance of some small mammals. The open-area specialists Cryptonanus chacoensis and C. scotti had a decrease in abundance, while D. albiventris and O. nigripes were favored by woody encroachment. Our data suggest that woody encroachment is shifting community composition: small mammals often associated with grasslands and open savannas are likely to be negatively affected by woody encroachment; while species that rely on tree covered habitats are likely to benefit from an increasing woody landscape. Therefore, forest-dwellers are gradually replacing open-vegetation inhabitants. Active management of open formations (e.g., with prescribed burning) may be needed to maintain Cerrado biodiversity, especially considering the open-area endemics.